Statistics for Policy and Planning in Canadian Higher Education: An Ontario Perspective - Creet, Mario; Trotter, Bernard (Canadian Journal of Higher Education, 1978)
Systems of information about higher education in Canada are in a mess. Substantively they are being developed on the basis of doubtful assumptions and confused purposes. Data for administrative and financial control are being confused with data needed for policy and planning purposes. Data systems are designed without due regard to practicality cost and need. A dubious passion for all purpose systems obscures the necessary role of special data sampling projects and special analyses in throwing light upon choices for the future. Planners and policy makers continue to act as if projection methods appropriate for the fifties are still sufficient for the future. Procedures for the development of information systems are being left to people who tend to be preoccupied with day-to-day and technical concerns, unrestrained by university and government policy makers who prefer to ignore or refuse to see that the gathering and presenting of statistical information acts directly on the policy and planning process. The demonstrated lack of interest by most senior leaders in government and in the universities in the assumptions, methods and procedures involved in collecting and analyzing information is illustrated by the failure of both universities and governments to develop separate or joint capacities for continuing analysis on a national basis of what is happening and why. Substantial work done at the provincial and regional level is not brought together for examination from a national perspective. If the universities do not themselves take corrective action, this failure will progressively reinforce the "provincialization" of universities so much deplored by academic leaders as being antithetical to the basic nature of authentic universities. The data needs associated with control should become the responsibility of provincial jurisdictions while the resources of Statistics Canada and the energy of AUCC should be oriented to policy information relating to global, national and interprovincial questions.